Mapeando os conflitos e as interações da agricultura urbana e planejamento urbano na cidade do Rio de Janeiro - Yago Evangelista Tavares de Souza (2023)
The idea that the city is a place of conflicts is something frequently reiterated in urban geography, especially in urban geography that aligns with the critical perspective. Understanding urban conflicts is a fundamental part of advancing geography as a science, and the issue of Urban Agriculture presents itself as a challenge, not only because it deviates from the expected norms of urban environments, but also because it remains largely underexplored within urban geography as a whole. In this sense, there still exists a gap in the connection between public policies, governance, urban planning, and Urban Agriculture. Studies are lacking that inquire whether master plans influence Urban Agriculture, but more importantly, studies that engage in dialogue with urban farming movements and inquire how the difficulties posed by urban planning have been overcome. This dissertation aims to study the relationship between urban agriculture and urban planning in the city of Rio de Janeiro. To achieve this goal, a review of relevant literature on Urban Agriculture was conducted, as well as a systematic review of urban legislation, particularly focusing on the master plans of the city of Rio de Janeiro. The purpose of this was to identify changes in recent years that intersect with the subject matter addressed in this project, particularly pinpointing areas of the city where agriculture is either encouraged or discouraged. A conflict related to participation in master plans by the group "A Cidade Também Planta" (The City Also Plants) is examined, as well as the impact of the implementation of the Pedra Branca State Park on local farmers. The situation in the Serra da Misericórdia is also addressed.